Mechanical approach of PP/MMT polymer nanocomposite - Dobrzánski, L. A. (2010)
Purpose: Paper summarizes and focus on investigation of PP/MMT nanocomposite in mechanical and statistical approach. Design/methodology/approach: Research has been performed basing on design of experiment. Findings: Considerable predominance of PP + nanoclay mixture in the increment of absorption of energy is found; Level of absorbed energy, required to break the specimens during fracture test is two times higher after structure reinforcement by nanoparticles. Research limitations/implications: Non-conventional injection moulding gives us possibility to control orientation level and develop morphology and it is limited due to non-conventional injection system limitation (pressure, time etc). Practical implications: PP/MMT nanocomposites are the materials with promising future wide range of application also in the specific branches like car and aircraft industries. Originality/value: Nanocomposites obtained in experiment obtaining allow to achieve shish-kebab structure, reinforce skin/core structure and improve mechanical behaviour.